2023
DOI: 10.1007/s13187-023-02326-4
|View full text |Cite
|
Sign up to set email alerts
|

Training Community African American and Hispanic/Latino/a Advocates on Prostate Cancer (PCa): a Multicultural and Bicoastal Approach

Abstract: African American communities are disproportionately impacted by prostate cancer (PCa) compared to other racial/ethnic groups. Whereas the incidence of PCa in Hispanic/Latino men is lower than the incidence in non-Hispanic/Latino White men, Hispanic/Latino men are more likely to be diagnosed with PCa in late stages, and less likely to be knowledgeable about PCa, resulting in significant disparities. We developed, culturally adapted, translated, implemented, and evaluated a PCa Cancer Advocacy Training in Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Regarding interventions for health literacy in this population, one study demonstrated that implementing culturally sensitive CHAs for prostate cancer resulted in signi cant increases in knowledge level. 15 This further validates the need for culturally sensitive interventions in this community to relieve cancer disparities. Additionally, discussions with physicians were associated with greater cancer knowledge and optimism about survival rates, further indicating the importance of culturally sensitive healthcare interactions.…”
Section: Culturementioning
confidence: 57%
See 3 more Smart Citations
“…Regarding interventions for health literacy in this population, one study demonstrated that implementing culturally sensitive CHAs for prostate cancer resulted in signi cant increases in knowledge level. 15 This further validates the need for culturally sensitive interventions in this community to relieve cancer disparities. Additionally, discussions with physicians were associated with greater cancer knowledge and optimism about survival rates, further indicating the importance of culturally sensitive healthcare interactions.…”
Section: Culturementioning
confidence: 57%
“…15 These CHAs possess a deep understanding of the cultural nuances prevalent within their communities, enabling them to offer tailored advice and support, and were shown to in uence increased medical knowledge in the community. 15 Medical mistrust also results in available free services being utilized less frequently. Many African American women rejected free cancer services, stating that they viewed it as associated with a perception of poverty and receiving charity.…”
Section: Culturementioning
confidence: 99%
See 2 more Smart Citations